Morphology and phytochemical potential of Vaccinium varingiifolium in Mount Lawu, Karanganyar District, Central Java, Indonesia - EFRI ROZIATY; SANTHYAMI SANTHYAMI; PUTRI AGUSTINA; IMA ARYANI; MUHAMMAD ASYAM FATHIN; SALSA ANIDA RAHMANIA; MUHAMMAD YAHYA NUR SHOLIHIN; DAWUD FA'I SALSABILLA (Society for Indonesian Biodiversity, 2025)
Abstract. Roziaty E, Santhyami, Agustina P, Aryani I, Fathin MA, Rahmania SA, Sholihin MYN, Salsabilla DF. 2025. Morphology and phytochemical potential of Vaccinium varingiifolium in Mount Lawu, Karanganyar District, Central Java, Indonesia. Biodiversitas 26: 3209-3217. Vaccinium varingiifolium, commonly known as Cantigi, is a subalpine shrub endemic to high-altitude ecosystems above 2,000 meters. Mount Lawu, located in Central Java, Indonesia, represents one of its key habitats. Despite its ecological relevance, the species remains underexplored, particularly in terms of its morphological and phytochemical traits. This study aimed to characterize the morphological features and phytochemical composition of V. varingiifolium to understand its adaptive strategies and ecological role better. A combination of qualitative and quantitative exploratory approaches was employed, using purposive sampling. Morphological assessments, including microscopic examinations, were conducted on stems, leaves, flowers, and fruits. Phytochemical screening using spectrophotometry targeted secondary metabolites, while ecological observations assessed environmental factors influencing adaptation. Morphological characterization of V. varingiifolium in Lawu Mountains revealed that young leaves are purplish-red, turning green with increased tissue density upon maturation. Stems are brown, globular, and lignified. Flowers are purplish-red, bell-shaped (campanulate), and axillary in position. Fruits are oval (5-6 mm in diameter), transitioning from green to black as they ripen. Phytochemical analyses revealed the presence of flavonoids and tannins, compounds known for their antioxidant, antibacterial, anti-inflammatory, and wound-healing properties. The plant thrives at elevations of 2,900-3,100 meters, where higher temperatures facilitate rapid regeneration. These findings provide important insights into the morphological adaptations and chemical defenses of V. varingiifolium, supporting conservation initiatives and enriching our understanding of plant survival mechanisms in subalpine environments, particularly in the context of climate change.